Study on water resources consumption and environmental pollution of China's provinces under different economic development levels. (11th June 2021) - Zhang, Chenjun; Hua, Rui; Shi, Zhen; Chiu, Yung‐ho; Qin, Shijiong; Sun, Xinrui
Abstract: In China, the contradiction between rapid economic development and water shortage has attracted much attention. This paper explores the problems of water consumption and environmental pollution in provinces with different economic development levels in China. Sewage discharge is put into the undesirable meta frontier dynamic data envelopment analysis (DEA) model as an undesirable output variable. The water use efficiency under different income levels from 2013 to 2017 is compared at the provincial level from the perspective of domestic water use efficiency, ecological water use efficiency, industrial water use efficiency and agricultural water use efficiency, and the dynamic evolution is further revealed by using kernel density estimation. The results show that water resource utilisation efficiency is positively correlated with regional income level and economic development level. The internal differences in high‐income areas are narrowing, while the internal differences in middle‐income areas are significantly expanding; agricultural water use efficiency is the most prominent problem. In view of these situations, the total amount and intensity of water consumption should be controlled in high‐income areas. For middle‐income provinces with abundant water resources but low efficiency, local governments can strengthen legislation and supervision.